Mapk7 enhances osteogenesis and suppresses adipogenesis by activating Lrp6/β-catenin signaling axis in mesenchymal stem cells - Chuan Li; Jiahui Long; Shuqing Chen; Liru Tian; Ya Xiao; Shulin Chen; Deying Su; Baolin Zhang; Peiqiang Su; Liao Zhiheng; Caixia Xu (Communications Biology)
Abstract The lineage commitment and differentiation of mesenchymal stem cells (MSCs) play a crucial role in bone homeostasis. MAPK7 (Mitogen-activated protein kinase 7), a member of MAPK family, controls cell differentiation, proliferation and survival. However, the specific role of Mapk7 in regulating osteogenic and adipogenic differentiation of MSCs remains to be determined. In this study, depletion of Mapk7 in MSCs by crossing Prx1-Cre mice to Mapk7 flox/flox resulted in severe low bone mass and accumulation of fat in bone marrow exhibiting osteoporosis (OP) in mice. Mapk7 promoted osteogenic differentiation and inhibited adipogenic differentiation of MSCs after knocking out and over-expressing Mapk7 in vitro. Mechanistically, Mapk7 activated Wnt/β-catenin signaling by phosphorylating Lrp6 at Ser1490, which ultimately enhanced osteogenesis and suppressed adipogenesis of MSCs. This is of great clinical and scientific significance for understanding biological function of Mapk7 and developing potential therapeutic targets for treatment of MSCs differentiation imbalance related bone diseases, such as, osteoporosis.